Antioxidant and Free Radical Scavenging Activities of Curcumin - Asouri, Mohsen; Ataee, Ramin; Asghar Ahmadi, Ali; Amini, Abdolhossein; Rezaei Moshaei, Masoumeh (Asian Journal of Chemistry, 2013)
The imbalance between free radicals and the body's defenses against oxidative stress cause chronic diseases. With regards to beneficial properties of antioxidants to neutralize oxidative reactive products, the identification of more effective and less toxic antioxidant compounds is in progress. The aim of this study is to evaluate the antioxidant power of curcumin by two methods i.e., 1,1-diphenyl-2-picryl hydrazyl radical (DPPH) assay and reducing power activity (RPA), compared with ascorbic acid, a well known antioxidant. Percentage of free radical scavenging of curcumin and ascorbic acid was more than 69 and 62 % at concentration 0.1 mM, respectively. It was not observed any difference between curcumin and ascorbic acid in antioxidant potencies. These results showed excellent antioxidant activity for curcumin and it is main reason for biological activities of curcumin.